Implementasi Pengembangan Integrated Curriculum di SMP Muhammadiyah Plus Klaten Utara - Gunagraha, Shindid; Yusgiantara, Akbar; Haryadi, Yaniz Naura Naviana; Hanifa, Azzahra Sabrina (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
This study aims to examine how the innovation of curriculum system development in educational institutions is carried out by integrating several curriculum references in improving the quality of education. Educational institutions are required to provide a wide space to facilitate students in developing competencies broadly to face increasingly complex problems. In the digital era, every individual is required to always adapt to social conditions and environmental changes that are accelerating. The curriculum must be adapted to the evolving situation and conditions and become a step, direction and process to achieve educational goals. This research was conducted using a field descriptive qualitative research method. The location of the research is in the Muhammadiyah Plus North Klaten Junior High School. The results of the study show that there is an integrated curriculum development in SMP Muhammadiyah Plus Klaten Utara by combining three curricula that are a reference in academic development. Integrating the curriculum of officials, organizations, and pesantren which is carried out through student learning activities.